Neural circuit mechanisms linking courtship and reward in Drosophila males. - Shen, P.; Wan, X.; Wu, F.; Shi, K.; Li, J.; Gao, H.; Zhao, L.; Zhou, C. (Current Biology, 2023)
Courtship has evolved to achieve reproductive success in animal species. However, whether courtship itself has a positive value remains unclear. In the present work, we report that courtship is innately rewarding and can induce the expression of appetitive short-term memory (STM) and long-term memory (LTM) in Drosophila melanogaster males. Activation of male-specific P1 neurons is sufficient to mimic courtship-induced preference and memory performance. Surprisingly, P1 neurons functionally connect to a large proportion of dopaminergic neurons (DANs) in the protocerebral anterior medial (PAM) cluster. The acquisition of STM and LTM depends on two distinct subsets of PAM DANs that convey the courtship-reward signal to the restricted regions of the mushroom body (MB) ? and ?/? lobes through two dopamine receptors, D1-like Dop1R1 and D2-like Dop2R. Furthermore, the retrieval of STM stored in the MB ?'/?' lobes and LTM stored in the MB ?/? lobe relies on two distinct MB output neurons. Finally, LTM consolidation requires two subsets of PAM DANs projecting to the MB ?/? lobe and corresponding MB output neurons. Taken together, our findings demonstrate that courtship is a potent rewarding stimulus and reveal the underlying neural circuit mechanisms linking courtship and reward in Drosophila males.